2014
DOI: 10.1155/2014/469308
|View full text |Cite
|
Sign up to set email alerts
|

Modified Block Pulse Functions for Numerical Solution of Stochastic Volterra Integral Equations

Abstract: We present a new technique for solving numerically stochastic Volterra integral equation based on modified block pulse functions. It declares that the rate of convergence of the presented method is faster than the method based on block pulse functions. Efficiency of this method and good degree of accuracy are confirmed by a numerical example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To solve deterministic IEs or SIEs, a variety of numerical approaches are developed. Bernstien polynomials [8,9], orthonormal Bernoulli polynomials (OBPs) [10], block pulse functions [11], Chebyshev wavelets [12], Legendre polynomials [13], shifted Jacobi operational matrix [14], shifted Legendre polynomials [15], meshless local discrete Galerkin scheme [16], wavelets Galerkin method [17], generalized hat basis functions [18], Legendre wavelets Galerkin method [19], Chebyshev cardinal wavelets [20,21], and so on are utilized to determine the solution for different types of IEs.…”
Section: Introductionmentioning
confidence: 99%
“…To solve deterministic IEs or SIEs, a variety of numerical approaches are developed. Bernstien polynomials [8,9], orthonormal Bernoulli polynomials (OBPs) [10], block pulse functions [11], Chebyshev wavelets [12], Legendre polynomials [13], shifted Jacobi operational matrix [14], shifted Legendre polynomials [15], meshless local discrete Galerkin scheme [16], wavelets Galerkin method [17], generalized hat basis functions [18], Legendre wavelets Galerkin method [19], Chebyshev cardinal wavelets [20,21], and so on are utilized to determine the solution for different types of IEs.…”
Section: Introductionmentioning
confidence: 99%
“…The improved block-pulse function is introduced by Farshid Mirzaee [41]. These modified block-pulse functions are applied to numerical solution of stochastic Volterra integral equations [42]. The Bernstein polynomials (BPs) and improved block-pulse functions (IBPFs) are introduced in [43].…”
Section: Introductionmentioning
confidence: 99%
“…Asgari et al suggested stochastic operational matrix based on Bernstein polynomials for obtaining numerical solution of nonlinear stochastic integral equation [7]. K.Maleknejad et al used modified block pulse functions for solving stochastic Volterra integral equations [8].S. Bhattacharya et al have obtained numerical solutions of Volterra integral equations by applying Bernstien polynomials [9].…”
Section: Introductionmentioning
confidence: 99%